Sistema electoral web para el Instituto Superior Tecnológico Luis Tello del cantón Esmeraldas (Innovation & Development in Engineering and Applied Science, 2022)
This article is based on the design of a website for the student elections process of the Luis Tello Higher Technological Institute (ISTLT) of the Esmeraldas canton. For this, a bibliographic process was used to support the current use of communication and information security through the Internet in electoral processes. For the design of the interfaces and database of the site, an incremental modeling was applied in which gradual functionalities were added in the successive refinements made to the system such as pages through Google Sites, a tool that although it is free and easy to use, has drawbacks for the development of highly professional websites. The developed system is reliable and offers a friendly interface for the user in the massive handling of online information, complying with the security posture of the websites created exclusively against the suspicious credibility of the massive handling of online information.